Development of a bioprinter-based method for incorporating metabolic competence into high-throughput in vitro assays - Hopperstad, Kristen; Deisenroth, Chad (Frontiers in Toxicology, 2023)
The acceptance and use of in vitro data for hazard identification, prioritization, and risk evaluation is partly limited by uncertainties associated with xenobiotic metabolism. The lack of biotransformation capabilities of many in vitro systems may under- or overestimate the hazard of compounds that are metabolized to more or less active metabolites in vivo. One approach to retrofitting existing bioassays with metabolic competence is the lid-based Alginate Immobilization of Metabolic Enzymes (AIME) method, which adds hepatic metabolism to conventional high-throughput screening platforms. Here, limitations of the lid-based AIME method were addressed by incorporating bioprinting, which involved depositing S9-encapsulated microspheres into standard 384-well plates with requisite cofactors for phase I and II hepatic metabolism. Objectives of this study included: 1) compare the lid-based and AIME bioprinting methods by assessing the enzymatic activity of a common cytochrome P450 (CYP) enzyme, 2) use biochemical assays with the bioprinting method to characterize additional measures of phase I and II metabolic activity, and 3) evaluate the bioprinting method by screening 25 chemicals of known metabolism-dependent bioactivity in the VM7Luc estrogen receptor transactivation (ERTA) assay. A comparison of the two methods revealed comparable precision and dynamic range. Activity of additional CYP enzymes and glucuronidation was observed using the AIME bioprinting method. The ERTA experiment identified 19/21 ER-active test chemicals, 14 of which were concordant with expected biotransformation effects (73.7%). Additional refinement of the AIME bioprinting method has the potential to expand high-throughput screening capabilities in a robust, accessible manner to incorporate in vitro metabolic competence.